Advances in high permeability polymer-based membrane materials for CO2 separations. Issue 6 (13th April 2016) - Wang, Shaofei; Li, Xueqin; Wu, Hong; Tian, Zhizhang; Xin, Qingping; He, Guangwei; Peng, Dongdong; Chen, Silu; Yin, Yan; Jiang, Zhongyi; Guiver, Michael D.
Abstract : This review summarizes the major advances since 2012 in highly permeable and CO2 -selective polymer-based membrane materials. Abstract : Membrane processes have evolved as a competitive approach in CO2 separations compared with absorption and adsorption processes, due to their inherent attributes such as energy-saving and continuous operation. High permeability membrane materials are crucial to efficient membrane processes. Among existing membrane materials for CO2 separations, polymer-based materials have some intrinsic advantages such as good processability, low price and a readily available variety of materials. In recent years, enormous research effort has been devoted to the use of membrane technology for CO2 separations from diverse sources such as flue gas (mainly N2 ), natural gas (mainly CH4 ) and syngas (mainly H2 ). Polymer-based membrane materials occupy the vast majority of all the membrane materials. For large-scale CO2 separations, polymer-based membrane materials with high CO2 permeability and good CO2 /gas selectivity are required. In 2012, we published a Perspective review in Energy & Environmental Science on high permeability polymeric membrane materials for CO2 separations. Since then, more rapid progress has been made and the research focus has changed significantly. This review summarises the advances since 2012 on high permeability polymer-based membrane materials for CO2 separations. The major features of this review are reflected in the following three aspects: (1) we cover polymer-based membrane materials instead of purely polymeric membrane materials, which encompass both polymeric membranes and polymer–inorganic hybrid membranes. (2) CO2 facilitated transport membrane materials are presented. (3) Biomimetism and bioinspired membrane concepts are incorporated. A number of representative examples of recent advances in high permeability polymer-based membrane materials is highlighted with some critical analysis, followed by a brief perspective on future research and development directions.